PROGRAM PENGEMBANGAN IDE UMKM WAROENG KOPI SINGGAH - Septi Anti; Fitriatus Solikah; Sholehatul Mardiyah (LP2M Universitas Ibrahimy, 2021)
Waroeng Kopi Singgah is a coffee shop that focuses on selling coffee on Pilang Street No.200, Wonoayu Sidoarjo. The sales location is strategic, but during this pandemic period it has decreased so that there is a lack of interest in visitors to come to the coffee shop to stop by. The purpose of implementing this program is to increase knowledge about making suitable product brands, knowledge about how to market through digital marketing, an increase in products with various variants, and an increase in turnover after selling through various online media. To achieve the expected goal, a series of activities were carried out using the PAR (Particitory action research) approach method, with various stages in its implementation, namely 1). Planning, this stage is carried out offline observation and identification of problems that are being experienced by the owner of the Singgah coffee shop. 2). Implementation, carrying out a series of activities from rebranding to marketing through digital marketing, and 3). Evaluation, assessment of the work program implemented. The result of the implementation of this activity is the presence of a new logo reflecting the stopover coffee shop, the existence of two coffee variants, namely arabica and robusta. In addition, there is promotion by making digital marketing through online media such as nstagram and shopee. Through a series of activities, it is hoped that there will be an increase in turnover and wider product recognition through online media.